2013
DOI: 10.1590/s1807-55092013005000004
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho coordenativo de crianças: construção de cartas percentílicas baseadas no método LMS de Cole e Green

Abstract: Os propósitos do estudo foram: 1) apresentar valores de referência percentílica às quatro provas da bateria de testes KTK; 2) comparar o desempenho coordenativo entre crianças vouzelenses e de outros estudos do país e exterior; e 3) apresentar pseudo-curvas de velocidade para cada prova. Foram avaliadas 811 crianças com idades entre os seis e os 10 anos. O desempenho coordenativo foi estimado por meio da bateria KTK. Cartas percentílicas e pseudo-curvas de velocidade foram construídas com base no método LMS, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
3
5
0
2
Order By: Relevance
“…33 Whilst children generally improve their GMC with age, 34 in the current study, a nonlinear trend in GMC across time was found suggesting a performance peak at 9 years of age, that is, the exponent of age square remains negative in all models. Yet, available reports on GMC centile charts in Portuguese children 35,36 do not clearly show a plateau around 9 years of age. Our finding is perhaps due to the fact that our serial data stop at 9 years.…”
Section: Yearsmentioning
confidence: 92%
“…33 Whilst children generally improve their GMC with age, 34 in the current study, a nonlinear trend in GMC across time was found suggesting a performance peak at 9 years of age, that is, the exponent of age square remains negative in all models. Yet, available reports on GMC centile charts in Portuguese children 35,36 do not clearly show a plateau around 9 years of age. Our finding is perhaps due to the fact that our serial data stop at 9 years.…”
Section: Yearsmentioning
confidence: 92%
“…It is worth emphasizing that in the present study the increase occurred between six and eight years of age; and after that, the curves showed either a constant increase in the subtest scores, or a plateau. Chaves et al 3 , when analyzing the pseudo-speed curves for the four KTK battery tests, suggested that there might be a reduction in the annual gains for motor proficiency between 6 and 10 years of age, and these changes may be specific to each test and might be associated with gaps in motor learning opportunities. For example, the strong interindividual variability is expressed in values ranging between the P3 and the P97 in the different subtests.…”
Section: Discussionmentioning
confidence: 99%
“…Motor proficiency is key to a healthy development, as low motor proficiency in childhood has been associated with anxiety and depression, poor social skills and low self-esteem, lower quality of life, low cardiorespiratory fitness and obesity. Given these negative association, early identification of problems through effective assessment for further intervention is extremely important 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Para avaliar os níveis de DM de crianças e jovens foi aplicado um conjunto de testes oriundos das baterias da EUROFIT (6) , AAHPER (1) e Fitnessgram® (33) As cartas percentílicas para os testes de DM foram construídas separadamente para cada sexo com base no método LMS (7) , implementado no software LMSchartmarker Pro versão 2.54 (26) . Resumidamente, o método LMS permite que a distribuição de dados independentes com valores positivos possa ser normalizada recorrendo à transformação Box-Cox.…”
Section: Testes De Desempenho Motorunclassified
“…Os graus de liberdade e a qualidade no ajustamento dos modelos, para cada sexo e prova, foram determinados de acordo com o sugerido por Pan e Cole (25) , Royston e Wright (29) e van Buuren e Fredriks (32) . Considerada uma ferramenta estatística muito atual e com vantagens claras relativamente a outros métodos de estimação (6,27) , O perfil das curvas percentílicas construídas neste estudo é muito semelhante ao referido noutros estudos nacionais e internacionais (1,4,5,14,24,28,31) .…”
unclassified